Potato Peels and Mixed Grasses as Raw Materials for Biofuel Production - Omar, Shaaban Z.; Hasan, Ayad H.; Lalov, Ivo (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
Biogas and fuel ethanol are renewable energy sources, can be produced from complex organic materials that are decomposed by microorganisms in the anaerobic digestion method. Potato peels (PPs) and mixed Lolium perenne and Dactylis glomerata grasses were assessed as a potential substrate for biomethanation in a batch method under mesophilic condition (35°C) and ethanol fermentation. The first approach of this work was focused on pretreatment of PPs using acidic and enzymatic hydrolysis to produce biogas and ethanol fermentation using Saccharomyces cerevisiae and Safbrew S-33. These experiments proved that enzymatic hydrolysis produced 1.2 g/L of ethanol involved 115 h of fermentation and 665 ml/h of biogas after 451 h of biomethanation, this was more than the outcomes of acidic treatment. The second approach was concentrated on ability of biogas and ethanol production from mixed grasses treated with different acid concentrations that produced 0.16 g/L ethanol over 8 days of fermentation and 500 ml/h of biogas after 13 days of methanation technique. In general, the results pointed out that PPs and combined grasses can be used as potential substrates with raw materials for biogas and ethanol production.